Jordan Economy under the EU Association Agreem Implementations - Khlaf, Dr. Bilal; Lyon, Bob (Dirasat in Economics and Business, 2004)
There has been a shift in many countries since the early 1980s towards a greater reliance on the market mechanism. This of course reflects a recognition that interventionist politics are often not only inefficient, but also ineffective and counterproductive. A major policy issue facing many of the countries of the Mediterranean (Med) region is to follow the rest of the world in liberalizing, privatizing, and deregulating markets. Economic reform efforts undertaken by many countries of the region in the last decade have been gradual and piecemeal.